From microverse to metaverse : modelling the future through today's virtual worlds - Evans, Leighton; Frith, Jordan; Saker, Michael (Bingley, U.K. : Emerald Publishing Limited, 2022)
While the metaverse is often marketed as a future utopia, the vision of the metaverse represents an attempt for private corporations to control the code of the real. In the hands of companies that established and maintain the surveillance capitalism model, the ability to build a persistent, all-compassing environment means all activity in that world can be metricized and commodified, making the metaverse worthy of critical examination. Significant parts of life are already conducted in a digital place that combines various aspects of digital culture. Likewise, digital worlds for socializing already exist, and in a form akin to the VR metaverse, just as VR worlds based on play now coexist with online worlds of user generated content. These discreet private "microverses", as we refer to them, are spaces which can model the tensions that would be inherent in the metaverse. From Microverse to Metaverse: Modelling the Future through Today's Virtual Worlds examines the place attachments, world-feeling and dwelling of several "microverses" to assess the possibilities of the metaverse as a realistic proposition. Critically analyzing the phenomenological feeling of place, the political economy of emerging tech, the mechanisms of identity and self along with the behavioral constraints involved, the authors map what a metaverse might be like, whether it can happen, and just why some companies seem so determined to make it happen.
Chapter 1. Introduction -- Chapter 2. The roots of the metaverse -- Chapter 3. Social worlds -- Chapter 4. Gaming worlds -- Chapter 5. User generated worlds -- Chapter 6. Worlds of commerce -- Chapter 7. Worlds of desire -- Chapter 8. Entertainment worlds -- Chapter 9. Fitness worlds -- Chapter 10. Conclusion - building the world we want to build.
Includes bibliographical references and index.
Keywords: Virtual reality; Virtual reality -- Social aspects; Virtual reality -- Political aspects; Forecasting -- Computer simulation; Social Science -- Sociology -- General; Virtual reality